Sexual dimorphism and morphometric study of Caspian pond turtle, Mauremys caspica (Testudines : Geoemydidae) in Golestan Province, southeast of the Caspian Sea - Yazarloo, M.; Kami, H.G.; Bagherian Yazdi, A. (Caspian Journal of Environmental Sciences, 2017)
The Caspian pond turtle, Mauremys caspica, is a terrapin belonging to family Geoemydidae. Totally, 130 specimens (67 males and 63 females) were collected manually and by net from different aquatic habitats in Golestan Province from 2016 through 2017. Morphometric characteristics such as length were measured using digital caliper and weight by electronic weighting scale. Skin of this turtle was dark olive green in color and had rows of longitudinal yellow stripes around the head and neck. Their carapace was relatively flat, the bridges between the dorsal and ventral shells were bony, and the ends of anal scutes were found to be pointed. Fingers and toes had swimming membranes. Sexes were identified using the location of vent on the tail. Sex ratios of males to females were nearly 1:1. The maximum straight carapace length (SCL2) was 80.66-230.16 (156.72 ± 42.93) and 56.96-236.84 (147.02 ± 50.76) in males and females, respectively. Ratios of SCL2 to maximum plastron length (PL2) were found to be 1.013- 1.32 (1.15 ± 0.04) in males and 1.01-1.15 (1.08 ± 0.03) in females; ratios of SCL2 to straight carapace width (SCW) were 1.24-2.60 (1.40 ± 0.16) in males and 1.20-1.47 (1.35 ± 0.07) in females; ratios of SCL2 to carapace height (CH) were 2.28-3.55 (2.79 ± 0.22) in males and 2.05-8.78 (2.87 ± 1.11) in females; ratios of SCL2 to tail length2 (TL2) were 2.33-7.59 (3.76 ± 0.91) in males and 2.34-4.78 (3.06 ± 0.62) in females. Ratios of straight width of femuro-anal suture (FASW) to anal seam length (AnSL) were 2.95–5.89 (3.78 ± 0.54) in males and 2.65-4.13 (3.23 ± 0.40) in females. The ratio of TL2 to TL1 and TL1 to RBrL are found to be the fast and simple grouping index to determine sex of the specimens.